Eletrodeposição de ligas de Ni-W sobre aço carbono: caracterização dos filmes - Zacarin, Maria Gabriela (2023)
The electrodeposition of Ni-W alloy on steel substrate from acid and alkaline solution containing NTA as a complexing agent for Ni2+ and WO4 2- ions was initially studied. EDX analyzes of the galvanostatically produced films found that from the complex formed between Ni-NTA there was no unloading of Ni2+ ions and, therefore, there was no alloy formation. Therefore, studies of the Ni-W alloy were conducted in acidic and alkaline ion solutions in the presence of aspartic acid, which complexes the Ni2+ ions, and also from the acid solution containing the boric acid-sorbitol complex from which the Ni2+ remains free in solution. The complexation of Ni2+ ions with aspartic acid shown in the species distribution diagram was evidenced by the results obtained in the UV-Vis and in the potentiometric titration. The voltammetric analyzes of the tested solutions observed that the increase in the nickel concentration in the deposition bath, pH variation and variation in the composition of the deposition bath did not influence the control of the reduction process of the Ni-W alloy. SEM analysis of the Ni-W electrodeposits produced with qd = 40.00 C cm-2 showed that the films were smooth, cracked or had globular crystallites depending on the composition of the bath and the deposition current density (jd) studied. EDX analyzes of the Ni-W electrodeposits found that the W content varied with the jd studied and with the composition of the deposition bath. The XRD analyzes indicated, in general, that the solid solution of W in Ni was designed independently of the deposition bath and the jd, and also through XRD analysis, the calculated grain size showed that the W content presented in the films evolved in different grain sizes. The testicles of adhesion of the films visited that, for the most part, the Ni-W films had good adhesion to the steel substrate. Open circuit potential (Eca) studies as well as polarization studies have found that Ni-W films protect steel from corrosion